Stenotrophomonas maltophilia bacteremia in adult patients with hematological diseases: clinical characteristics and risk factors for 28-day mortality - Wenjing Guo; Qingsong Lin; Jia Li; Xiaomeng Feng; Sisi Zhen; Yingchang Mi; Yizhou Zheng; Fengkui Zhang; Zhijian Xiao; Erlie Jiang; Mingzhe Han; Jianxiang Wang; et al. (Microbiology Spectrum)
ABSTRACT Patients with hematological diseases are at high risk for Stenotrophomonas maltophilia (SM) bacteremia. This study retrospectively analyzed the clinical characteristics and risk factors for 28-day mortality among 140 adult hematological patients diagnosed with SM bacteremia from January 2012 to July 2023. he overall 28-day mortality was 31.43% (44/140), with a median age of 44 years. The median hospital stay before SM bacteremia onset was 25 days, and 69.29% of patients had unresolved neutropenia. All patients had received broad-spectrum antibiotics in the past month, and 69.29% developed breakthrough bacteremia during carbapenem therapy. Independent risk factors for mortality included a Sequential Organ Failure Assessment (SOFA) score ≥5, tigecycline exposure, age ≥60, and pulmonary infection. Patients with ≥2 risk factors were stratified into the high-risk group, with a significantly higher 28-day mortality compared with the low-risk group (56.52% vs 7.04%, P < 0.001). Treatment with trimethoprim-sulfamethoxazole (TMP/SMX) (P = 0.008) or TMP/SMX combined with cefoperazone/sulbactam (CSL) (P = 0.005) was associated with survival benefits among high-risk patients. Overall, SM bacteremia usually occurs in hematological patients with prolonged hospitalization, unresolved neutropenia, and extensive use of broad-spectrum antibiotics, especially carbapenems. Patients with high SOFA scores, advanced age, pulmonary infection, or recent tigecycline exposure are at higher risk of mortality. The preferred treatment is TMP/SMX rather than fluoroquinolones, with combination therapy of TMP/SMX and CSL considered a feasible treatment option.IMPORTANCEThis study, representing the largest cohort of adult hematological patients with SM bacteremia to date, strengthens the validity of existing findings and provides new insights into its clinical management. We identify risk factors for 28-day mortality, revealing that patients with two or more risk factors experience particularly high mortality rates. This highlights the importance of early identification and targeted management of high-risk individuals. Our findings also demonstrate that TMP/SMX is superior to fluoroquinolones and suggest that combining TMP/SMX with CSL may offer additional survival benefits.